2017
DOI: 10.1007/s00264-017-3703-z
|View full text |Cite
|
Sign up to set email alerts
|

Mini-subvastus versus medial parapatellar approach for total knee arthroplasty: a prospective randomized controlled study

Abstract: The mini-subvastus approach could offer faster recovery, less pain and shorter hospital stays without compromising the principles of proper prosthesis position and limb alignment compared with the medial parapatellar approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…The HKA angle was used to assess the lower limb force line and the FFC and FTC angles were used to assess the prosthetic position. The ideal values of the HKA, FFC, and FTC were 180˚, 96˚ and 90˚, respectively (8). In addition, prosthetic position deviation and limb alignment deviation within 5˚ were considered to be within an acceptable range (8).…”
Section: Methodsmentioning
confidence: 99%
“…The HKA angle was used to assess the lower limb force line and the FFC and FTC angles were used to assess the prosthetic position. The ideal values of the HKA, FFC, and FTC were 180˚, 96˚ and 90˚, respectively (8). In addition, prosthetic position deviation and limb alignment deviation within 5˚ were considered to be within an acceptable range (8).…”
Section: Methodsmentioning
confidence: 99%
“…Jang et al [20] reported that preand post-operative hip-knee-angle, post-operative American Knee Society (AKS) and the Western Ontario and McMaster Universities (WOMAC) score were significant predictors for subjective satisfaction in patients undergoing opening-wedge high tibial osteotomy. Mini-subvastus approach could offer faster recovery, less pain, and shorter hospital stays without compromising the principles of proper prosthesis position and limb alignment compared with the medial parapatellar approach of TKA [21]. Zha et al [22] retrospectively analyzed the relationship between chondromalacia patellae (CMP) and post-operative anterior knee pain (AKP).…”
Section: Yingze Zhangmentioning
confidence: 99%
“…Such approaches include the Sub-Vastus (SV), mid-vastus, and minimal incision surgical techniques [3,4]. The SV approach described by Hofmann et al [1] in 1991 leaves the quadriceps intact and completely attached to the medial patellar border, which theoretically reduces pain associated with violating the extensor mechanism and lessens the risk of blood supply damage to the patella and subsequent avascular necrosis and fractures of the patella [5,6]. Such benefits may improve the range of movement and functional outcomes of patients after TKA surgery [7].…”
Section: Introductionmentioning
confidence: 99%
“…Opponents of the SV approach, however, claim that the approach is associated with surgical difficulties such as gaining adequate exposure of the surgical field and everting the patella especially in obese and muscular patients, which may result in mechanical axis deviation and increased complications [8,9]. Several studies comparing the SV and MPP approaches suggested faster rehabilitation with increased knee flexion and reduced pain [5,6,10,11], but other reports showed no difference between the two surgical approaches [12][13][14].…”
Section: Introductionmentioning
confidence: 99%